(3GdJbGVj GdGdcJQhfj aj GdYbhO GdGdcJQhfjIs - (3hGFd MeOj(B, (3CMeOs ((3GdefUhQI(B:s (3OGQ GdacQ h GdbGfhf ddfTQ hGdJhRjY(B,s, 2010)
(3JWhQ TQW GdJMcje GdGdcJQhfj h GdGMcGe GdJj JfcQ gPG GdJMcje GJaGb GdJMcje GdhGQO aj QSGFd Ch HQbjGJ eJHGOdI , GdGMcGe GdbVGFjI GdJj WHbJ YHGQI QSGdI Ch HQbjI , eQGcR GdJbGVj GdGdcJQhfj , WHjYI GdJMcje GdGdcJQhfj , GdGYJQGa HCMcGe GdJMcje GdGdcjQhfj h JfajPgG , bGfhf GdChfSJQGd GdfehPLj ddJMcje GdJLGQj GdOhdj, bhGYO GdCjcGfs
(3edGMb U(B.155s
Keywords: (3GdJMcjes; (3GdJMcje GdEdcJQhfjs; (3GdYbhOs